The Effect of Capital Structure, Operating Cash Flow, and Activity Ratio on the Profitability of Agricultural Companies Listed on the Indonesia Stock Exchange - Arifuddin Lamusa; Nelson Metubun; Mohammad Zubair Hipy (Cita konsultindo, 2025)
Microeconomics provides a theoretical framework for understanding how a company achieves profit margins, while profit margin is a key measure of performance that reflects the effectiveness of a company's microeconomic strategy, including in agricultural companies. This study aims to analyze the influence of capital structure, operating cash flow, and activity ratio on the profitability of agricultural companies listed on the Indonesia Stock Exchange, especially Crude Palm Oil (CPO) companies. The research approach is quantitative using secondary data from 11 Crude Palm Oil (CPO) agricultural companies for the 2021-2024 period, so that the total data is 44 research data. Data collection uses documentation, namely accessing the official website of the Indonesia Stock Exchange. Data analysis uses multiple regression analysis of panel data. The results of the study show that simultaneously, the capital structure (Debt to Equity Ratio), operating cash flow, and activity ratio (inventory turnover) together have a significant effect on profitability (Net Profit Margin) in Crude Palm Oil (CPO) agricultural sector companies listed on the Indonesia Stock Exchange with a determination coefficient of 81.2172%. While the remaining 18.7828% is explained by other variables that are not studied in this study such as operational cost efficiency, sales and revenue growth levels, raw material prices or production inputs, tax policies and interest expense and price strategies and product competitiveness in the market. Then partially, the capital structure (Debt to Equity Ratio) has a negative and insignificant effect on profitability (Net Profit Margin), operating cash flow has a positive and significant effect on profitability (Net Profit Margin), and activity ratio (inventory turnover) has a positive and significant effect on Profitability (Net Profit Margin).